The Use of soil amendments in crop production: A review - Enguwa, Kuume; Horn, Lydia; Awala, Simon (Namibian Journal for Research, Science and Technology, 2024)
The fertility status of the Namibian soils is very low. In some parts of the country, such as the semi-arid Central Namibia, this phenomenon is much more extreme and, hence, a significant setback for crop growers. The soils are primarily sandy and lack organic matter, further worsened by low precipitation, high temperatures, and high evapotranspiration rates. This paper provides a background on soil amendments, including the two primary ways of categorising them based on the origin and the composition of the material(s) forming the amendments. Secondly, it offers a historical overview of the general agricultural use of soil amendments. Lastly, the paper discusses different soil amendments currently used and their effects on the fertility and productivity of agricultural soils. It is recommended that the effectiveness and the optimal application ratios of locally available soil amendments for crop production be studied. Keywords: Soil amendments, soil health, crop production, climate change, semi-arid, Namibia